Technical solutions to improve global sustainable management of waste electrical and electronic equipment (WEEE) in the EU and China - Euan Long; Saskia Kokke; Donald Lundie; Nicola Shaw; Winifred Ijomah; Chih-Chuan Kao (Journal of Remanufacturing, 2016)
With the amount of Waste Electrical and Electronic Equipment (WEEE) being generated every year and increasing at an accelerating rate, the management of electronic waste (e-waste) has become an important global issue. This article contains a literature survey and a practical study of five mobile phones. In the literature survey WEEE management approaches in the EU and China were evaluated to identify differences and commonalities in approach as well as the identification of the current best practices. Practical End-of-Life (EoL) treatment processes, including remanufacturing, reconditioning, repairing, recycling, repurposing, reusing and disposal of e-waste were all investigated and studied in context of mobile phones. In the phone disassembly exercise the component material, weight, joining method, possibility of re-attachment and damage of disassembly were identified and noted down for every removed component. This disassembly gave insight in how the WEEE management in the EU could be adapted to improve the amount of component recovery. A final suggestion is to implement an EU objective open-access component database where original equipment manufacturer (OEM) component data and updated component performance information can be found. This would improve the quality and identification of components and hence aid component recovery.
Keywords: 650; WEEE policy; EU; China; EoL treatment; Mobile phones; Design for disassembly